Optimization of Fermentation Technology and Determination of Physicochemical Properties of Pure Malt Wine - Kai WANG; Yisheng LAN; Yu HUANG; Wenmei ZHAO; Yuqi CHEN; Yali WU; Nan LI (Shipin gongye ke-ji, 2022)
Pure malt wine was brewed from germinated malt by semi-solid fermentation technology, and the process optimization and physicochemical properties were determined. The single factor experiment was designed to study the effects of fermentation time, inoculation amount of koji and addition amount of glucoamylase on the alcohol content of pure malt wine, and to determine the best single factor. The experimental conditions were studied after the single factor level determination, meanwhile the orthogonal design was carried out, and the optimal combination was determined as follows: fermentation time of 4 d, inoculation amount of 2‰ koji and addition amount of 2% glucoamylase. Under these conditions, the alcohol content of pure malt wine was 10.6%vol±0.3%vol, the total phenol content was 1.159±0.066 g/L, the protein content was 209.568±19.178 mg/L, the total acid content was 6.4±0.2 g/L, reducing sugar content was 8.409±0.021 g/L, the scavenging rate of hydroxyl radical was 86.75%±1.42%, and the total reduction capacity could reach 1.842±0.004. Through the analysis of variance of orthogonal experiment, it was concluded that fermentation time and glucoamylase dosage had significant effect on the alcohol content of pure malt wine (P<0.05), while inoculation amount had no significant effect on the alcohol content of pure malt wine (P>0.05). The results would provide a theoretical basis for the production and development of pure malt wine.